Olfactory neuroblastoma: the long-term outcome and late toxicity of multimodal therapy including radiotherapy based on treatment planning using computed tomography - Mori, Takashi (Radiat Oncol, 2015)
BACKGROUND: Olfactory neuroblastoma (ONB) is a rare tumor originating from olfactory epithelium. Here we retrospectively analyzed the long-term treatment outcomes and toxicity of radiotherapy for ONB patients for whom computed tomography (CT) and three-dimensional treatment planning was conducted to reappraise the role of radiotherapy in the light of recent advanced technology and chemotherapy. METHODS: Seventeen patients with ONB treated between July 1992 and June 2013 were included. Three patients were Kadish stage B and 14 were stage C. All patients were treated with radiotherapy with or without surgery or chemotherapy. The radiation dose was distributed from 50 Gy to 66 Gy except for one patient who received 40 Gy preoperatively. RESULTS: The median follow-up time was 95 months (range 8–173 months). The 5-year overall survival (OS) and relapse-free survival (RFS) rates were estimated at 88% and 74%, respectively. Five patients with stage C disease had recurrence with the median time to recurrence of 59 months (range 7–115 months). Late adverse events equal to or above Grade 2 in CTCAE v4.03 were observed in three patients. CONCLUSION: Multimodal therapy including radiotherapy with precise treatment planning based on CT simulation achieved an excellent local control rate with acceptable toxicity and reasonable overall survival for patients with ONB.